An Analysis of Attitude of Men Folk and Family Disputes in Pakhtun Society: A Case Study in Malakand (Pakistan) (Journal of Asian Development Studies, 2023)
This research endeavors to examine the challenges confronted by educated women in the workforce and their correlation with family conflicts, particularly focusing on the attitudes of men in Malakand, Pakistan. The cultural norms in the Pukhtun community make it challenging for educated women to pursue employment, as patriarchal structures hinder their involvement in the public domain, subjecting them to various restrictions. Utilizing a quantitative research design, the study employed a well-structured questionnaire for data collection, with a sample size of 384 respondents chosen through random sampling. The collected data were analyzed using SPSS version 21, applying bivariate and multivariate tests to assess the association between independent variables and the study's outcome variables. The findings indicated a significant association (P≤0.05) between family disputes and factors such as husbands' encouragement of their wives, the dominance of working wives in domestic decisions, husbands' participation in domestic activities, husbands displaying rude behavior, increased likelihood of conflicts over household chores, husbands exhibiting authoritative behavior, and husbands' involvement in external household activities impacting their relationship with working wife. The study proposes that women should be actively encouraged to engage in all aspects of life, including equal employment opportunities and respect.